Vaccination Strategy Analysis with SIRV Epidemic Model Based on Scale-free Networks with Tunable Clustering. Issue 3 (January 2021) - Meng, Xueyu; Cai, Zhiqiang; Dui, Hongyan; Cao, Huiying
Abstract: In this paper, we propose an SIRV (susceptible, infected, recovered, vaccination) evolutionary game model for infectious disease vaccination strategies based on the scale-free networks with tunable clustering. This model takes into account factors such as vaccination effectiveness, vaccination cost, treatment cost after illness, government subsidy rate and treatment discount rate. First of all, we use the idea of evolutionary game to make each individual in the network get two strategies, including vaccination and non-vaccination. Meanwhile, in each propagation process, according to the policy update rule (PUR), each individual updates its game strategy according to the benefit relationship with the adjacent nodes. Then, we analyze the compulsory and voluntary vaccination on the scale-free network with considering the influence of vaccination efficiency, the cost of vaccination, the cost of treatment after illness, the government subsidy rate, the treatment discount rate on vaccination. The results indicate that when the vaccination effectiveness is about 0.9, it is a better value for the evolution of vaccination strategy. For government decision making, choosing appropriate values of s and d can make the overall benefit of society higher.